2016
DOI: 10.18576/ijnc/020103
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis and Optimisation of Silver Nanoparticles by the Endophytic Fungus Cladosporium sphaerospermum

Abstract: The present study is dealing with an ecofriendly and green biological route for extracellular biosynthesis of silver nanoparticles (AgNPs) using the endophytic fungus Cladosporium sphaerospermum F16 (KU199685). The biosynthesised AgNPs were characterised using ultraviolet-visible spectroscopy (UV-vis), transmission electron microscopy (TEM), dynamic light scattering (DLS), energy-dispersive X-ray analysis (EDX) and X-ray diffraction (XRD). The results showed the formation of stable, well-dispersed and spherica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 44 publications
0
23
0
1
Order By: Relevance
“…The results of the nano-Ag as antifungal agent were consisted with few earlier reports293189. The important advantages of Ag NPs-based antimicrobial agents are their biocompatibility, health and environmental safety, and their excellent stability6389 reported that; the mycosynthesized AgN Ps at (5 and 10 ppm) exhibited a more effective activity in inhibiting the mycelia growth of pathogenic strains of Alternaria solani , the causal agent of tomato early blight disease as compared to the recommended chemical fungicide used (Ridomil gold plus 2 g/l).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The results of the nano-Ag as antifungal agent were consisted with few earlier reports293189. The important advantages of Ag NPs-based antimicrobial agents are their biocompatibility, health and environmental safety, and their excellent stability6389 reported that; the mycosynthesized AgN Ps at (5 and 10 ppm) exhibited a more effective activity in inhibiting the mycelia growth of pathogenic strains of Alternaria solani , the causal agent of tomato early blight disease as compared to the recommended chemical fungicide used (Ridomil gold plus 2 g/l).…”
Section: Discussionmentioning
confidence: 62%
“…These fungal cells was washed extensively using Milli-Q deionized water to remove any medium component and 10.0 g (wet weight) of fungal cells were added to 100 ml distilled water in an Erlenmeyer flask and agitated again at 200 rpm for 48 hr at 30 °C. Then, the cell filtrate (periplasmic fraction) was obtained by filtering through Whatman filter paper2942. The pellet was re-suspended in 5 ml cold 50 mM PBS at pH 7.0 and sonicated on ice with the power level set about 4–5, at 40–50% duty for 15–20 bursts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-free filtrate without AgNO 3 solution was also run as a control. 31 AgNPs dispersion was then centrifuged at 14,000 rpm for 20 min. The supernatant was discarded, and the pellets were redispersed in distilled water, and washed three times with sterilized distilled water to remove the free entities and unbound biological molecules from AgNPs.…”
Section: Biosynthesis Of Agnpsmentioning
confidence: 99%
“…45 Several groups have utilized the crude extract of fungi for myco-synthesis of AgNPs. 31,46,47 Different studies have discussed the fabrication of AgNPs based on fungi-assisted bioreduction processes, as well as their antibacterial activities. 20,48,49 The fungus Fusarium sp.…”
Section: Biosynthesis and Characterization Of Agnpsmentioning
confidence: 99%